1999
DOI: 10.1038/sj.gt.3300957
|View full text |Cite
|
Sign up to set email alerts
|

Development of human papillomavirus plasmids capable of episomal replication in human cell lines

Abstract: Gene delivery into human cells has been facilitated by the plasmids containing the viral E1 and E2 genes (or the E1 development of viral vector systems. These vectors have gene alone) and an origin of replication were shown to repshown great potential for the efficient delivery of theralicate to significant levels in the transfected human cervical peutic genes into human cells. A problem with many of the carcinoma C-33A cell line. Since approaches towards the existing systems, however, is the integration of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
(29 reference statements)
0
2
0
1
Order By: Relevance
“…The pZF HpV  + F N genotype may be sub-cloned using similar PCR-primers to the ones proposed above for consortia plasmids, with tailored modifications to HPV plasmids or PsV. Sverdrup et al [43] have previously generated such human papillomavirus (HPV) plasmids containing the viral E1 and E2 genes (or the E1 gene alone) and an origin of replication, which they simultaneously demonstrated to replicate to significant levels in the transfected human cervical carcinoma C-33A cell line. Alternatively, HPV PsV encapsidation of the zinc finger consortium’s plasmids carrying the pZF HpV  + F N (see results of modeling above) may suffice.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…The pZF HpV  + F N genotype may be sub-cloned using similar PCR-primers to the ones proposed above for consortia plasmids, with tailored modifications to HPV plasmids or PsV. Sverdrup et al [43] have previously generated such human papillomavirus (HPV) plasmids containing the viral E1 and E2 genes (or the E1 gene alone) and an origin of replication, which they simultaneously demonstrated to replicate to significant levels in the transfected human cervical carcinoma C-33A cell line. Alternatively, HPV PsV encapsidation of the zinc finger consortium’s plasmids carrying the pZF HpV  + F N (see results of modeling above) may suffice.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…For example, newer BPV-1 based vectors contain only the LCR and the E1 and E2 genes (Mannik et al, 2002;Ohe et al, 1995) and are maintained in transgenic mice for several generations (Mannik et al, 2003). Human papillomavirus-based vectors have also been explored and shown to be able to replicate, at least transiently, in human cell lines and in the lungs of mice (Gadi et al, 1999;Sverdrup et al, 1999). However, at this point these studies have shown mainly "proof of principle" of papillomavirus based vectors and they have not yet been widely or practically used to express foreign genes.…”
Section: F Papillomavirus-based Vectorsmentioning
confidence: 99%
“…Η πρωτεΐνη αυτή είναι απαραίτητη για την ιική DNA αντιγραφή, καθώς προσδένεται στο σηµείο έναρξης της αντιγραφής του ιικού γονιδιώµατος στην LCR περιοχή[Stunkel & Bernard 1999]. Έχει δειχτεί ακόµη, πως προσδένει ATP καθώς και την πλήρους µεγέθους E2, η οποία ονοµάζεται και E2 διεγέρτης της µεταγραφής (E2 transcription transactivator, E2TA), ώστε να εντείνει την ιική µεταγραφή[Sverdrup et al 1999]. Ωστόσο, κάποια προϊόντα εναλλακτικής ωρίµανσης αυτού του ORF, λειτουργούν σαν καταστολείς της µεταγραφής[Chiang et al 1992].…”
unclassified